Enhanced optoelectronic properties of Ti-doped ZnO nanorods for photodetector applications. Issue 17 (1st September 2021) - Ade, Ramesh; Kumar, S. Sathish; Valanarasu, S.; Kumar, S. Saravana; Sasikumar, S.; Ganesh, V.; Bitla, Yugandhar; Algarni, H.; Yahia, I.S.
Abstract: We report the effect of Ti-doping on structural, morphological, photoluminescence, optical and photoconductive properties of ZnO thin films. Pure and Ti(1, 3 and 5%)-doped ZnO thin films are deposited by the successive ionic layer adsorption and reaction (SILAR) method. The X-ray diffraction analysis revealed the single-phase hexagonal wurtzite ZnO structure of all the films. Scanning electron microscope images suggest the formation of rod shaped particles in Ti-doped ZnO thin films. Photoluminescence spectra of all the films show emission peaks centered at 398 nm, 413 nm, 438 nm, 477 nm and 522 nm wavelengths. Optical properties support the semiconducting nature of all the films. The optical bandgap values are estimated to be 3.29 eV, 3.26 eV, 3.19 eV and 3.23 eV for ZnO, ZnO:Ti(1%), ZnO:Ti(3%) and ZnO:Ti(5%) thin films, respectively. Photoconductivity study indicates that ZnO:Ti(3%) thin film exhibits high responsivity, external quantum efficiency and detectivity of 0.30 AW -1, 97% and 5.49 × 10 10 Jones, respectively, among all the films. The enhanced photoconductivity of Ti-doped ZnO thin films make them useful for optoelectronic applications.